Epidemiological profile of fatal burn cases in tertiary care centre of Lucknow: An observational study - Kumar Yadav, Pradeep; Kumari, Sangeeta; Kumar Verma , Anoop; Singh, Raghvendra; Rupani, Raja; Shiuli; Chaudhary, Richa; Singh, Mousami (Journal of Indian Academy of Forensic Medicine, 2020)
Burn is one of the most common injuries which has been recognized as public health problem. It affects nearly every population and every geographical zone in the world and have always been considered as one of the most destructive injuries, causing not only morbidity and mortality but also major economic and psychological impacts. This study intends to explore the medicolegal aspects and recent epidemiological trends of burn cases. This is an autopsy based cross sectional observational study from a period of August 2015- July 2016 and was carried out in the department of Forensic Medicine and Toxicology, King George’s Medical University, Lucknow, Uttar Pradesh. Cases were thoroughly studied using specially designed proforma that include demographic profile of deceased, history from relatives, police and hospital records and autopsy findings. A total of 550 burn cases were studied for which significant information regarding epidemiological and medicolegal aspects have been obtained. Out of 550 cases, majority were females 70.18%. Male: Female ratio was 1:2.35. The age of the victims ranged from age 7 months to 84 years and mean age was 28.98+11.65 years. Most common affected age group was 21-30 years (47.45%). Majority of cases were married. A statistically significant (p=0.019) higher proportion of married cases were found among female. Majority of the cases were housewives (60.97%), followed by students (15.80%), farmers (11.52%), businessmen (4.83%) and laborers (4.46%). Majority of the cases, 82.55% occurred at home and only 2.91% at workplaces, rest 14.55% cases occurred elsewhere. The majority of the cases occurred in Summer and Winters seasons (38.91%and37.91%), while least number of cases were seen during Monsoon season (6.36%). Majority of burn injuries were found to occur between 2:00 pm -10:00 pm. Flame was the most common type of causative agent in males as well as in females, however difference in causative agent of burn injuries of female and male cases was found to be statistically significant (p<0.001). Most common percentage of TBSA involved was >80% (36.73%), while in 2.18% cases %TBSA was 1-20%. Commonest manner of death among burn injury cases was found to be accidental. And also, among accidental cases, proportion of males was higher than females, while proportion of females was higher in homicidal and suicidal cases. This study highlights the parameters that should make the clinician reassess the course of treatment, warning that the patient might be critically near death. For example, the probability of sepsis increases with prolonged ICU stay. Patient’s age and % TBSA affect the mortality of post trauma victim.